Performance modelling and analysis of the assembly line system of leaf spring manufacturing plant using Petri nets. (3rd November 2022) - Parkash, Shanti; Tewari, P.C.
This work describes the performance modelling and analysis of the assembly line system of leaf spring manufacturing plant. Availability is considered as a performance measure which is the function of reliability and maintainability of the plant. This work focuses on the use of reliability, availability, maintainability and safety (RAMS) tool which can reduce the uncertainties of the plant availability using certain software. It covers all stages of the product development process. Simulation and modelling among four subsystems in varying conditions is done by a Petri module of GRIF software. This work investigates effect of varying repair and failure rates of different subsystems on the performance of a system in terms of availability. Decision support system (DSS) has been proposed for this system. The outcomes of this paper might be helpful for the maintenance department to provide priorities for the critical subsystem which can help to increase the system performance.